Relevansi Video Youtube Dengan Materi Pembelajaran Sains Kelas IV SD/MI - Wardani, Fina (Journal Of Islamic Elementary School (JIES), 2016)
This research aims to explain the relevance of the video on Youtube with learning materials science class IV SD / MI. Data were collected using keywords and on certain criteria, such as many viewer and viewer response. The analysis used is the video content analysis. The conclusion was that (1) some videos on Youtube have relevance to the material science class IV, but much past the assessment stage as a due diligence phase of learning materials. (2) Youtube video selected can be used as learning materials, but need to do some repairs. (3) Youtube video can be used as a secondary learning materials, so there needs to be a primary learning materials derived from textbooks are more standardized.